2020
DOI: 10.1177/0894845319900938
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Moderated Mediation Model of Turnover Intentions With Chinese Employees

Abstract: This study explores the role of organizational career growth on employees’ organizational identification and turnover intentions in the contemporary career era. We compare the impact of organizational career growth and perceived external prestige of organization on employees’ organizational identification and turnover intentions and probe whether perceived alternative job opportunities moderate the relations between perceived external prestige–organizational identification and organizational career growth–orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…The relationship between TI and PAJO is positive, while the relationship between PAJO and organizational identification is negative. Organizational identification is also a mediator in the negative relationship between perceived external prestige and organizational career growth with TI (Zhu, Flores, Weng, & Li, 2020). In a study conducted among nurses, perceived job alternatives were found to moderate the relationship between job engagement and turnover intention (Zhou, et al, 2022).…”
Section: Review Of Recent Studiesmentioning
confidence: 99%
“…The relationship between TI and PAJO is positive, while the relationship between PAJO and organizational identification is negative. Organizational identification is also a mediator in the negative relationship between perceived external prestige and organizational career growth with TI (Zhu, Flores, Weng, & Li, 2020). In a study conducted among nurses, perceived job alternatives were found to moderate the relationship between job engagement and turnover intention (Zhou, et al, 2022).…”
Section: Review Of Recent Studiesmentioning
confidence: 99%
“…The concept of occupational prestige (OPP) refers to employees’ perceptions of how the public perceives their occupation ( Zhu et al, 2020 ). The OPP is also defined as organisational members’ opinions and perceptions of how outsiders assess their organisational position and reputation ( Mael and Ashforth, 1992 ; Rathi and Lee, 2016 ), and it is also known as an employee’s perception of the organisational status among others ( Dalton et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Career growth differs from organizational career growth as the former captures the growth of overall career duration and reflects both intra-organizational and inter-organizational career growth (Table 9). Scholarly literature has posited variables including emotional stability, personality traits (Jiang et al, 2020a(Jiang et al, , 2020b, organizational socialization learning (Spagnoli, 2020) as antecedents and turnover intentions (Weng and McElroy, 2012;Zhu et al, 2020) and voice behavior (Wang et al, 2014) as consequences of organizational career growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Contextual influences studied as moderators include climate-like constructs, such as innovation climate (Jiang et al, 2020a(Jiang et al, , 2020b, job insecurity climate (Kang et al, 2019), perceptions on organizational politics (Wanniarachchi et al, 2020;Liu et al, 2010) and shared vision (Huang et al, 2017). The career-related moderators examined are career growth (Ingusci et al, 2019), career growth opportunities (Bashir et al, 2020) and perceived alternative job opportunities (Zhu et al, 2020). Scholars focused on individual characteristics such as political skill (Liu et al, 2010;Wei et al, 2012), self-efficacy (Xie et al, 2020) and individual adaptability (Ingusci et al, 2019) as moderators, along with personality-related variables such as proactive personality (Zhao et al, 2016).…”
Section: Integrative Reviewmentioning
confidence: 99%
See 1 more Smart Citation